If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 12 + -7(x + -4) + x = -12 Reorder the terms: 12 + -7(-4 + x) + x = -12 12 + (-4 * -7 + x * -7) + x = -12 12 + (28 + -7x) + x = -12 Combine like terms: 12 + 28 = 40 40 + -7x + x = -12 Combine like terms: -7x + x = -6x 40 + -6x = -12 Solving 40 + -6x = -12 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-40' to each side of the equation. 40 + -40 + -6x = -12 + -40 Combine like terms: 40 + -40 = 0 0 + -6x = -12 + -40 -6x = -12 + -40 Combine like terms: -12 + -40 = -52 -6x = -52 Divide each side by '-6'. x = 8.666666667 Simplifying x = 8.666666667
| 2.5z=46 | | -60+20x=20x+-20x | | 0.7x+0.15x=62 | | 3(5p-9)-4(p+7)= | | -7(1+n)=-1+5n | | 35*3x+4=70 | | -7(x+4)-42=8-29 | | 6x+22=22+6x | | 4n+2(n+10)=62 | | 1/2d+7=8 | | 6x-18=2x-10 | | H-27=3.5 | | 2(1-1x)=0 | | 9+5w-14w=12-6 | | 3(x+4)=6(x-2) | | -4y^3-8xy^4=-4y^4(1+2xy) | | A-13.4=2.6 | | 100x-200=50x-5 | | 3m+6-25=-22 | | 10(-3-2t)+10-2(6+13)=0 | | (-2x)(x+3)+(3x)(x-2)=-27 | | 0.10(100)+15=0.15(100)+x | | 45-5n+5= | | f(x)=5x^2-x+20 | | 8x^2-20x+25=0 | | x+122=2x+80 | | -29=5w-4 | | 4(2x-3)+7=x+5+x | | -4(5x+10)=-180 | | 0=12x^2-4x^3 | | 11+17-6x=2 | | 3x+14=94 |